PRIVILEGIETS PROBLEM - MELLEM DEN HUMANITÆRE OG DEN KYNISKE FORNUFT - Sharma, Devika (K&K - Kultur og Klasse, 2013)
THE PREDICAMENT OF PRIVILEGE: BETWEEN HUMANITARIAN AND CYNICAL REASON | In this article I explore a contemporary structure of feeling closely but ambivalently related to what moral anthropologist Didier Fassin has termed ”humanitarian reason”. I label this specific affective disposition ‘the predicament of privilege’. In the first part of the article I relate the predicament of privilege to various critiques of humanitarianism for being a ”feeling culture” depoliticizing questions of inequality, justice and social conflict. The latter part of the article examines ”the predicament of privilege” by way of analyzing a recurring Danish TV-fundraiser in terms of the various ugly feelings represented, produced and circulated by this particular charity show. My overall suggestion is that we can hardly understand the affective-moral dimensions of globalization without exploring the cultural forms and social functions of the ugly, unprestigious and amoral feelings pertaining to being globally privileged: sentiments such as boredom, indifference, compassion fatigue, cynicism, bad conscience and sheer reluctance to engage emotionally in the ethical claims made on us.